PRO DAN KONTRA TERHADAP HUKUM RIBA DALAMPERSPEKTIF I’JAZ TASYRI’ - Putri Ega Aulia; Aisyah Nurul Aini; Harun Al Rasyid (JOURNAL OF LAW AND NATION, 2024)
This study explores the cotroversial debate about the halalness of usury in Islamic economics, encompassing both pro and con arguments as well as perspectives from i’jaz tasyri' and the views of Islamic scholars and experts. Its objective is to analyze various viewpoints on riba, spanning from economic considerations to religious perspectives within the context of Islam, and to present arguments both in favor of and against the practice of riba. Data were gathered through literature review from diverse sources, including works by Islamic scholars and researchers, the Quran,and Islamic economic literature. The primary finding highlights the diverse nature of the debate regarding the permissibility of riba in Islamic economics, with proponents emphasizing its economic benefits such as investment incentives and financial stability, while opponents underscore social inequality, moral concerns, and the potential for economic instability. The main contribution of this research lies in presenting a comprehensive analysis of the riba debate within the framework of Islamic economics, integrating perspectives from economic, religious, and legal standpoints,and outlining financial alternatives aligned with Islamic principles, thus offering fresh insights for understanding this issue